Faktor Human, Organisasi dan Teknologi terhadap Kelengkapan Pengisian Dokumentasi Asuhan Keperawatan Melalui Rekam Medis Elektronik - Ghazali, Imam; Peristiowati, Yuly; Puspitasari, Yenny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the influence of human, organizational, and technological factors on the completeness of nursing care documentation through Electronic Medical Records (EMR) at RSUD Waru Pamekasan. The method used is observational with a cross-sectional approach. The population consists of all nursing staff at RSUD Waru Pamekasan, totaling 108 individuals, and a sample of 108 individuals was obtained using total sampling techniques. The measurement tool employed is a questionnaire, and the data analysis used is ordinal regression testing. The results show that human and technological factors have significant values; specifically, the human factor has a p-value of 0.001 with an Odds Ratio (OR) of 1.022, while the technological factor has a p-value of 0.000 with an OR of 1.065. This indicates that the technological factor has a greater influence than the human factor on the completeness of nursing care documentation through electronic medical records at RSUD Waru Pamekasan. In conclusion, the technological factor has a more significant impact compared to the human factor on the completeness of nursing care documentation through electronic medical records. This suggests that the quality and ease of use of technology are more crucial to the success of documentation than the skills or behaviors of nurses. Keywords: Completeness of nursing care, Organization, Electronic Medical Records, Technology, Human.